Corneal Subbasal Nerve Density and Sensitivity After Pars Plana Vitrectomy Using Contact or Noncontact Wide-Angle Viewing Systems. Issue 9 (September 2018) - Tosi, Gian Marco; Bacci, Tommaso; Tarantello, Antonio; Martone, Gianluca; Traversi, Claudio; Marigliani, Davide; Cevenini, Gabriele; Virgili, Gianni
Abstract : Purpose: To assess corneal subbasal nerve density (SBND) and corneal sensitivity (CS) after pars plana vitrectomy (PPV) for rhegmatogenous retinal detachment (RRD) without intraoperative 360-degree laser treatment using contact or noncontact panoramic viewing systems. Methods: This is a prospective study of 34 eyes affected by RRD, which underwent PPV using contact (18 eyes) and noncontact (16 eyes) panoramic viewing systems; 12 eyes which underwent scleral buckling, and 17 eyes which underwent cataract surgery. SBND and CS were assessed before surgery and 3 and 6 months postoperatively by in vivo confocal microscopy and Cochet–Bonnet esthesiometry. Results: Compared with baseline values, at 6 months, SBND and CS decreased in both contact PPV (SBND preoperative value: 19.1 ± 3.7 mm/mm 2 ; SBND postoperative value: 3.5 ± 1.3 mm/mm 2 ; CS preoperative value: 5.1 ± 0.5 cm; CS postoperative value: 1.5 ± 0.4 cm) and in noncontact PPV groups (SBND preoperative value: 19.5 ± 3.8 mm/mm 2 ; SBND postoperative value: 8.7 ± 2.3 mm/mm 2 ; CS preoperative value: 5.3 ± 0.5 cm; CS postoperative value: 2.5 ± 0.7 cm) ( P < 0.001 for all comparisons). SBND reduction was greater in the contact PPV group than in the noncontact PPV group ( P < 0.001). By contrast, the scleral buckling and cataract surgery group values were unchanged ( P > 0.1 for all comparisons). In multivariate analysis, no significant effect was found for cataract surgery associated with PPV, pseudophakia, surgical time, intraocular pressure, or for laser in horizontal sectors for PPV groups. SBND was highly correlated with CS (r = 0.93). Conclusions: A contact viewing system reduces SBND after PPV more than a noncontact system does.